ACCURACY AND ACCEPTABILITY OF THE WELLERMAN’S FOLKSONG TRANSLATION - Luqman Rosyidi; Ulayya, Putri Itsna; Afifah, Miftah Nur; Anam Sutopo; Dwi Haryanti (PT. Banjarese Pacific Indonesia, 2024)
An English folksong entitled The Wellerman became popular in Indonesia recently. Therefore, the accuracy and acceptability in folksong were important to be investigated. This paper reported the accuracy and acceptability of English into Indonesian translation in a folksong entitled The Wellerman. This research applied descriptive qualitative method. In addition, this research combined with purposive sampling technique. Nababan translation quality assessment framework was used to investigate the accuracy and acceptability of the folksong. The whole The Wellerman’s lyrics consist of 28 lines which was then assessed by the raters in terms of its accuracy and acceptability. The raters were 2 translators and 1 writer. The raters were purposely chosen to conduct reliable results of the accuracy and acceptability. This study found the average score of the accuracy was 2. 35 with 198 total scores and the average score of the acceptability was 2.48 with 209 total scores. The result indicates that the translation was relatively accurate and acceptable for the raters. However, it needs further improvement to maintain the context of the source text (ST) in the target text (TT) to reach an accuracy and acceptability in The Wellerman folksong. This study implied that it is crucial to maintain the imagery, narration, and the context of folksong translation.